Optimization of Cogging Torque in a Permanent Magnet Generator Using Magnet Shaping and Stator Dummy Slot Methods for a 10 kWp Wind Power Plant - Nur Pratama, Yuandika; Nur, Tajuddin (Syntax Corporation, 2026)
This research aims to optimize the performance of a permanent magnet generator by reducing cogging torque. Cogging torque is the torque generated due to the interaction between the tangential force at the edge of the magnets and the material in the stator slots. High cogging torque can hinder the rotor movement in permanent magnet generators. In wind power applications, cogging torque must be minimized as it can obstruct the turbine's rotation in the generator. Therefore, magnet shaping and dummy slot methods are applied in the optimized design construction of the permanent magnet generator using FEMM 4.2 software for 2D design and numerical analysis. The permanent magnet generator design utilizes 24 stator slots and 20 rotor magnetic poles with five different design configurations. In the second design configuration, using the magnet shaping method, a 53% reduction in cogging torque was achieved. In the third design, which employs both magnet shaping and rectangular dummy slots, a decrease of 99.30% was obtained. The fourth design, using magnet shaping and triangular dummy slots, resulted in a 92.4% reduction. In contrast, the fifth design, using magnet shaping and semicircular dummy slots, achieved a 95.5% reduction in cogging torque compared to the initial structure.